2020
DOI: 10.3390/foods9030350
|View full text |Cite
|
Sign up to set email alerts
|

Arthrospira platensis as Natural Fermentation Booster for Milk and Soy Fermented Beverages

Abstract: Arthrospira platensis, commercially known as Spirulina, is a fresh-water cyanobacterium that has been gaining increasing attention in recent years due to its high biological and nutritional value. For this reason, it has been employed in several food applications, to obtain or enhance functional and technological properties of cheese, yogurt, bread, cookies or pasta. The aim of this work was to evaluate the potential boosting effect of two different concentrations (0.25% and 0.50% w/v) of A. platensis on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…To the best of our knowledge, only the recent work of Martelli et al (2020b) focused on A. platensis fermentation in a non-dairy milk, specifically in a soybean drink. In accordance with the results obtained by Martelli et al (2020b) we have demonstrated that A. platensis can promote LAB growth. Similar results have also been reported by Bhowmik et al (2009), where the addition up to 10 g L −1 of A. platensis to MRS broth media containing different Lactobacillus cultures promoted the growth until 9 log CFU mL −1 (after 10 h), starting from a concentration of about 2.5 log CFU mL −1 .…”
Section: Suitability Of a Platensis Fandm-c256 Biomass For L Plantarusupporting
confidence: 92%
See 2 more Smart Citations
“…To the best of our knowledge, only the recent work of Martelli et al (2020b) focused on A. platensis fermentation in a non-dairy milk, specifically in a soybean drink. In accordance with the results obtained by Martelli et al (2020b) we have demonstrated that A. platensis can promote LAB growth. Similar results have also been reported by Bhowmik et al (2009), where the addition up to 10 g L −1 of A. platensis to MRS broth media containing different Lactobacillus cultures promoted the growth until 9 log CFU mL −1 (after 10 h), starting from a concentration of about 2.5 log CFU mL −1 .…”
Section: Suitability Of a Platensis Fandm-c256 Biomass For L Plantarusupporting
confidence: 92%
“…Several authors (de Caire et al, 2000;Varga et al, 2002;Bhowmik et al, 2009;Guldas and Irkin, 2010;Beheshtipour et al, 2013;Mazinani et al, 2016;Yamaguchi et al, 2019;Martelli et al, 2020b) evaluated the effect of Arthrospira spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A. platensis has been studied as a valuable source of antimicrobial, antiviral and antioxidant compounds but its activity is variable and dependent on the extractive solvent [ 58 , 59 , 60 ]. This cyanobacterium, commercially known as Spirulina, is used in food formulations or as a food supplement [ 6 , 61 ] and in health products [ 62 , 63 , 64 , 65 ], because of its composition rich in proteins and small peptides. The antimicrobial potential of small peptides is well known and the activity of several algae is related to their high protein content.…”
Section: Discussionmentioning
confidence: 99%
“…These types of drinks, alternative for probiotics, WPH progress the ability of lactic acid bacteria because it works for promoting the perfect viability of fermented milk products 14,15 . Besides, the addition of S. platensis into probiotic‐fermented dairy products will enhance the ability of probiotics and their functional characteristics because this cyanobacterium contains a huge quantity of nutrients taken into account “a functional food” 9,11 …”
Section: Introductionmentioning
confidence: 99%